2019
DOI: 10.1371/journal.ppat.1007499
|View full text |Cite
|
Sign up to set email alerts
|

INDETERMINATE-DOMAIN 4 (IDD4) coordinates immune responses with plant-growth in Arabidopsis thaliana

Abstract: INDETERMINATE DOMAIN (IDD)/ BIRD proteins are a highly conserved plant-specific family of transcription factors which play multiple roles in plant development and physiology. Here, we show that mutation in IDD4/IMPERIAL EAGLE increases resistance to the hemi-biotrophic pathogen Pseudomonas syringae, indicating that IDD4 may act as a repressor of basal immune response and PAMP-triggered immunity. Furthermore, the idd4 mutant exhibits enhanced plant-growth indicating IDD4 as suppressor of growth and development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 95 publications
2
47
0
Order By: Relevance
“…45 IDD4 is an integral part of the immune MAP kinase signaling pathway, and the MAP kinase MPK6 phosphorylates IDD4 as shown in in vitro kinase assays followed by LC-MS/MS analysis. 43 The MS/MS spectra for IDD4 revealed that MPK6 modifies the amino acid residue S-73 that has also been identified in several phosphoproteomic studies (Table 1). This phosphosite is conserved in all members of the IDD/BIRD family (Figure 1c).…”
Section: Idd/bird Proteins In Plant Immunitymentioning
confidence: 60%
See 4 more Smart Citations
“…45 IDD4 is an integral part of the immune MAP kinase signaling pathway, and the MAP kinase MPK6 phosphorylates IDD4 as shown in in vitro kinase assays followed by LC-MS/MS analysis. 43 The MS/MS spectra for IDD4 revealed that MPK6 modifies the amino acid residue S-73 that has also been identified in several phosphoproteomic studies (Table 1). This phosphosite is conserved in all members of the IDD/BIRD family (Figure 1c).…”
Section: Idd/bird Proteins In Plant Immunitymentioning
confidence: 60%
“…6 To unravel the biological function of these phosphosites, phospho-modified IDD4 versions were generated by substituting S-73 and T-130 by either alanine to obtain a phospho-dead version (IDD4-AA) or aspartic acid to obtain a phospho-mimicking (IDD4-DD) variant thereby purporting the unphosphorylated and the phosphorylated IDD4 conformation, respectively. 43 Phosphosite-mutated IDD4 plants show an opposite response to pathogen attack and transcriptome reprogramming and underscore the function of IDD4 in regulating genes related to immunity and plant growth. Chromatinimmunoprecipitation studies revealed the predominate binding of IDD4 to the ID1 motif 46 in close proximity to the transcriptional start sequence of putative target genes.…”
Section: Idd/bird Proteins In Plant Immunitymentioning
confidence: 94%
See 3 more Smart Citations